Anogenital Human Papillomavirus (HPV) Infection, Seroprevalence, and Risk Factors for HPV Seropositivity Among Sexually Active Men Enrolled in a Global HPV Vaccine Trial. (15th July 2021) - Tota, Joseph E; Giuliano, Anna R; Goldstone, Stephen E; Dubin, Brady; Saah, Alfred; Luxembourg, Alain; Velicer, Christine; Palefsky, Joel M
Abstract: Background: In men, the incidence of human papillomavirus (HPV)–related cancer is rising, but data regarding male HPV infection and seroprevalence are available from only a few countries. Methods: This analysis of a global HPV vaccine trial evaluated baseline data from 1399 human immunodeficiency virus–negative heterosexual men (HM) and men who have sex with men (MSM). Key objectives included assessment of HPV prevalence and risk factors for seropositivity to 9-valent HPV (9vHPV) vaccine types (6, 11, 16, 18, 31, 33, 45, 52, and 58), and concordance between seropositivity and prevalent HPV type. Results: Overall, 455 of 3463 HM (13.1%) and 228 of 602 MSM (37.9%) were HPV DNA positive for any 9vHPV vaccine type at baseline. Infection prevalence and seroprevalence (≥1 9vHPV vaccine type) were 13.2% and 8.1%, respectively, among 333 HM from Europe, and 37.9% and 29.9%, respectively, among 335 MSM from Europe or North America. Among men with baseline infection, MSM had higher seroprevalence for concordant HPV types (39.5% vs 10.8% in HM). The seropositivity risk (irrespective of baseline infection status) was higher among MSM versus HM (age-adjusted odds ratio, 3.0 [95% confidence interval, 2.4–6.4]). Among MSM, statistically significant seropositivity risk factors included younger age at sexual debut, higher number of receptive anal sex partners, and less frequent condom use. No factors assessed were associated with seropositivity in HM. Conclusions: Higher proportions of MSM than HM were HPV DNA positive and seropositive, and concordance between HPV DNA positivity and seropositivity, a potential marker of true infection versus carriage, was higher in MSM. Most MSM and HM were seronegative for all 9vHPV vaccine types, suggesting the potential benefit of catch-up vaccination after sexual debut. Clinical Trials Registration. NCT00090285. Abstract : Among sexually active men in a global vaccine trial, DNA prevalence and seroprevalence for 9-valent human papillomavirus vaccine types was higher in men who have sex with men (vs heterosexual men) but low overall, suggesting that catch-up vaccination may be beneficial.